Aberrant Auditory Steady-State Response of Awake Mice Induced by Chronic Interferon-α Treatment - Li, Yingzhuo; Wang, Xuejiao; Chen, Jingyu; Li, Zijie; Yang, Pingting; Qin, Ling (Frontiers in Pharmacology, 2021)
Background: Patients receiving the cytokine immunotherapy of interferon-alpha (IFN-α) frequently present with depression. This is one of the excellent models to explore the action of peripheral cytokine on central nervous system (CNS) and to study the development of depression. The auditory steady-state response (ASSR), electroencephalogram (EEG) oscillations induced by periodic acoustic stimulation, is an effective approach to evaluate the neural function in mental illness including depression. The aim of the present study was to investigate the effect of IFN-α on the cortical ASSR and its correlation with depressive-like behavior. Methods: Chronic electrodes were implanted on the skull over the auditory cortex (AC) of male C57BL/6 mice. The animals were treated with daily injection of IFN-α or saline (vehicle) for three weeks. EEGs were recorded in AC of the same mouse before and after the injection treatment to monitor the changes of ASSR induced by IFN-α. Depressive-like behavior was analyzed in the forced swim test (FST). Immunohistochemical staining was used to examine the status of neuron and glia in the hippocampus and AC. Results: Comparing to pretreatment condition, injection of IFN-α significantly reduced the power of 40-Hz ASSR in the mouse AC from the 2nd week. Such a decrease continued to the 3rd week. The immobility times of FST were significantly increased by a 3-week treatment of IFN-α and the immobility time was negatively correlated with the power of 40-Hz ASSR. Astrocytes and microglia in the hippocampus and AC were activated by IFN-α, but the density of neuron was not significantly affected. Conclusion: Our results suggest that EEG measurement of ASSR can be used as a biomarker to monitor the CNS side effects of IFN-α treatment and to search a novel intervention with potential therapeutic implications.